Assesment of static panel model of tourist demand in Croatia - Ivana Beljo; Kristina Devčić; Laura Pavelić (Elektronički Zbornik Radova Veleučilišta u Šibeniku, 2023)
Croatia is an important and widely recognizable tourist destination. The importance of tourism in Croatia is manifested in many aspects, and the share of income from tourism in BDP in Croatia is around 20%. The most numerous guests in Croatia are foreign guests, mostly from Germany, Austria, Slovenia, Italy and Poland. In this paper, foreign tourism demand in the Republic of Croatia was analyzed and impact of five selected variables on foreign tourism demand is estimated: gross domestic product of countries from which tourists come from, prices in Croatia, prices in competing countries, distance between countries and accommodation capacities. The analysis was carried out for the nine-year time period from 2010 to 2018 based on data for 32 countries from which tourists come, and OLS model, a panel model with fixed effects and a panel model with random effects were estimated. The adequacy of the model was tested with the Hausman test, Breusch-Pagan Lagrange test and F-test. A panel model with Driscoll-Kraay standard errors was estimated. The estimated model showed that the gross domestic product of the countries from which the tourists arrive has a statistically significant and positive influence on the foreign tourism demand in Croatia, while at a significance level of 10% the accommodation capacity in Croatia has a positive and statistically significant influence. The impact of other variables taken into account was not statistically significant.